Serum Total Superoxide Dismutase Activity as a Predictive Factor in Patients with Hepatocellular Carcinoma - Xu, Yanqiu; Liu, Bin; Cheng, Shiqing; Zhang, Junguo; Cao, Xiue; Wang, Yong; Luan, Fang (Hepatitis monthly, 2024)
Objectives: This study aimed to determine the cutoff value for diagnosis and predict mortality in hepatocellular carcinoma (HCC) based on serum total superoxide dismutase (SOD) activity. Methods: A retrospective case-control study of the SOD Model was conducted using data from a single-center dataset at Shandong Provincial Hospital Affiliated with Shandong First Medical University, China. Serum total SOD activity was analyzed in HCC patients (n = 124) and control subjects (n = 117). Receiver operating characteristic (ROC) curves were used to determine cutoff values of serum total SOD activity for HCC diagnosis. Overall survival (OS) was assessed using the Kaplan-Meier method. Results: In the model groups, the cutoff level of total SOD activity for HCC was 169.2 U/mL (sensitivity: 87.23%, specificity: 91.95%), while for HCC [alpha fetoprotein (AFP) < 20 ng/mL], it was 173.4 U/mL (sensitivity: 86.79%, specificity: 88.51%). Additionally, in the validation groups, the true positive rate, true negative rate, and accuracy rate were all above 90%. Based on the cutoff value of SOD, HCC patients were assigned to an H-SOD and L-SOD group depending on their serum total SOD activity at admission before operation. The 5-year OS rate of the H-SOD group was 75.00%, and that of the L-SOD group was 36.59% in HCC patients (P = 0.0245). With a decrease in SOD activity, serum levels of Zn (t = 3.890, P = 0.0003) and Se (t = 7.694, P < 0.0001) were also significantly decreased and positively correlated with SOD activity (both P < 0.05) in HCC patients. Conclusions: Low serum total SOD activity may also be a risk factor for HCC. The decrease of SOD activity in HCC patients was partly related to a lack of Zn and Se.